Development of slow release fertilizer from oil palm empty fruit bunch biopolymer composites - Ahmad Saffian, Harmaen (2016)
The use of fertilizers in agricultural sector has increased drastically along with the increasing food demand and world population. The high volume usage of conventional fertilizers is still rampant and it has brought a negative effect such as underground water pollution, environmental pollution, and health issues as well. At present, the utilization of chemical fertilizer in conventional fertilizer (broadcast system) such as nitrogen, phosphorus and potassium (NPK) has need 2.5 metric ton a year for an oil palm nursery. With application of slow released fertilizer (SRF) prepared using coating method, the usage has reduced to 1.8 metric ton per year. Furthermore, in order to extend the duration of SRF degradation release time, reduce the fertilizer cycle application. The industry seeks for new method of compounding to optimise the degradation and release rate. This study attempts to use twin screw extrusion method in compounding SRF that contains NPK fertilizer, biopolymer as well as the empty fruit bunch (EFB) fibre. EFB to improve the compatibility between biopolymer and NPK to produce good bonding of SRF composites beside it function as micro nutrient to the soil. The degradability of SRF composites is depending on the mechanism the NPK and EFB fibre in the twin screw barrel. It is anticipated that encapsulated at the outer layer of the mixture (EFB and NPK). Therefore, the encapsulate layer will be functional as slow released agent. The optimum processing temperature for all polymer used i.e. poly (lactic acid) PLA was 145- 150°C, poly (butylene succinate) PBS was 120-145°C, and poly (hydroxybutyrate-co-valerate) PHBv was 150-180°C. The speed of counter rotating twin screw extruder were set at 50 rpm and the feeder screw for NPK fertilizer, polymer and oil palm fibre was running at speed of 20 rpm. In this study, the formulation of BpF composites used comprises of polymer/NPK fertilizer (40/60%) and polymer/empty fruit bunch (EFB) fibres/NPK fertilizer (30/10/60%) ratio compounding. Scanning electron microscopy SEM was used to study dispersion of the EFB and fertilizer in the polymer. The morphological results showed that EFB and NPK distribution is well dispersed besides showed good bonding with the polymers. To ensure the effectiveness of the slow-release bioplastic fertilizer composite to be used in oil palm nursery, a biodegradation test was conducted. This test spanned over 24 weeks. Based on the results, the new invention of SRF composite namely as Biopolymer Fertilizer, (BpF) composite showed slower rate degradation rate as compared to pure NPK fertilizer. However BpF shown higher rate in degradation as compared to pure polymer mixed with NPK only. At early stage, of week 8, BpF composites experienced 40% of degradation for all formulation used. Continuous degradation until week 16 showed that BpF with the combination of PHBv/ EFB/NPK reached 100% of degradation. BpF made of PBS/EFB/NPK and PLA/EFB/NPK composite formulations have reached 80% degradation in week 24. BpF composites were further tested in leachate column in order to determine the reaction of BpF with water. From the study, all BpF composites have showed the nitrogen release between 15% and 40% at week 8 to 12. This elucidated the presence of reaction of the fertilizer in the composite systems. Nursery field test for 4-month old of oil palm seedlings was conducted. The results showed that the development and growth of the seedlings were excellent in terms of plant growth such as diameter, height, the number of fronds, and chlorophyll content. The growth of the seedlings applied with BpF was increased every week as compared to non BpF. The diameter and height with BpF composite is increased at the rate between 20% and 30%. The chlorophyll content increased around 20% with BpF composite. In conclusion, BpF composite has the potential as slow-release fertilizer in oil palm seedling nursery and thus reduce the relying of pure chemical fertilizer.